Źródła antropologii Juliana Haynesa Stewarda - Ryszard F. Sadowski (Studia Ecologiae et Bioethicae)
Julian H. Steward claims that he is the only author of an anthropological approach called cultural ecology and no one affected him in the process of working out the concept. However, this essay shows that there are three main sources that influenced Steward: social and natural environment, family and educational background, and intellectual community. All of these sources affected him on different levels but without their influence Steward would not create such an original concept of anthropological approach. M s essay points out the importance of Steward’s hard work on a farm during his study in Deep Springs College and the significance of the natural environment of California. It emphasizes the role of Steward’s parents, his college educators, and professors in Berkeley, as well as his personal experience during the Great Depression. Finally, this article describes the influence of the intellectual community on Steward, especially by F. Boas, A. Kroeber, and publications of T. R. Malthus, C. D. Forde, C. O. Sauer, and many others.